Integração de atividades experimentais e virtuais no ensino de circuitos elétricos através do jogo EletricGame - Figueiredo, Tatiane Lúcia Abreu de (2021)
This project is the result of research and application for the conclusion of the course in the National Professional Master's in Physics Education offered by the Brazilian Physics Society and developed in conjunction with the institutions UFAM and IFAM. Its main objective is to make physics classes attractive, efficient and enjoyable. Prepared for the subject of Electrical Circuits, it is sought from it that students are able to be protagonists in their significant learning process, for this reason expository classes were planned with alternation between board, experiments and simulators. Aiming beyond the teaching of concepts, theories and mathematical formalism, the contextualization and applicability of these terms in the student's experience, that is, that from the established dynamics, students can see Physics in their world. Transiting electrical circuits, current, potential difference and resistors, all activities culminated in the use of a game called EletricGame, created on the Scratch platform by the author of this work, in order to review everything that was learned and strengthen the knowledge obtained by participating students.